CONCEPTUAL PRINCIPLES OF SOCIALLY RESPONSIBLE ENTERPRISE MARKETING MANAGEMENT (AS EXAMPLE, SALES OF PAINTING MATERIALS) - Marina Klimchuk; Mariia Shehda (Izdevnieciba "Baltija Publishing", 2021)
Actuality of theme. In today's business becomes especially important concept of social responsibility, based on the principles of increased attention to social problems both customers and personnel. The main purpose of business activity - profit - achieved through the research needs of potential and actual customers, identify the public interest and the desire to satisfy them. The idea of social responsibility is an integral feature of the system of business in modern business practice of advanced countries. Scientists who researched social - responsible marketing are K.Keller, O.Hrishnova, A.Fedorchenko, P.Orlovoyi and others.